Strategi Pembelajaran Pendidikan Agama Islam Dengan Menggunakan Media Audio Visual Dalam Meningkatkan Prestasi Belajar Siswa Kelas VIII di SMP Islam Terpadu Syarif Hidayatullah Sukorambi Jember Tahun Pelajaran 2022/2023 - Zamzam, Jazirotu (Pendidikan Islam Pascasarjana IAIN Jember, 2023)
In the world of learning institutions, educators do not escape material studies and have strategies in conveying material to make it easier for students to understand the material. This study used a qualitative approach with the type of classroom action research (CAR) carried out through two cycles, each cycle carried out following the planning, acting, observing and reflecting procedures. Data collection techniques using observation, interviews and tests. The results showed: 1) Educators plan material as attractive as possible in conveying it through audio-visual media so that students experience an increase in student achievement with the following average scores: pretest I with an average score of 67.75 and pretest II 71.5 and posttest score I average value 79.65 and posttest II 87.8. The increase in student achievement can be seen in the N-gain values, namely: Ngain I 0.3402491 which is rounded up to 0.3 and N-gain II 0.5545 which is rounded up to 0.5. 2) Educators provide examples of behavior in the classroom so that they then assign assignments to students to foster an attitude of responsibility, confidence and discipline. 3) students experience development in terms of skills to explain their answers and in delivery they are no longer stammering. This is because students first understand the contents of the answers and examples.